Identification of a dysfunctional exon-skipping splice variant in GLUT9/SLC2A9 causal for renal hypouricemia type 2 - Toyoda, Yu; Cho, Sung Kweon; Tasic, Velibor; Pavelcová, Kateřina; Bohatá, Jana; Suzuki, Hiroshi; David, Victor A.; Yoon, Jaeho; Pallaiova, Anna; Šaligová, Jana; Nousome, Darryl; Cachau, Raul; et al. (Frontiers in Genetics, 2023)
Renal hypouricemia (RHUC) is a pathological condition characterized by extremely low serum urate and overexcretion of urate in the kidney; this inheritable disorder is classified into type 1 and type 2 based on causative genes encoding physiologically-important urate transporters, URAT1 and GLUT9, respectively; however, research on RHUC type 2 is still behind type 1. We herein describe a typical familial case of RHUC type 2 found in a Slovak family with severe hypouricemia and hyperuricosuria. Via clinico-genetic analyses including whole exome sequencing and in vitro functional assays, we identified an intronic GLUT9 variant, c.1419+1G>A, as the causal mutation encoding p.Gly431GlufsTer28, a functionally-null variant resulting from exon 11 skipping. The causal relationship was also confirmed in another unrelated Macedonian family with mild hypouricemia. Accordingly, non-coding regions should be also kept in mind during genetic diagnosis for hypouricemia. Our findings provide a better pathogenic understanding of RHUC and pathophysiological importance of GLUT9.